The Effect of Finishing and Polishing Systems on Surface Roughness and Microbial Adhesion of Bulk Fill Composites: A Systematic Review and Meta-analysis - Hoda Saleh Ismail; Ashraf Ibrahim Ali (Frontiers in Dentistry, 2023)
Objectives: This paper presents a systematic review and meta-analysis of the effect of different finishing and polishing (F/P) systems on surface roughness (SR) and microbial adhesion to bulk fill (BF) composites.